Towards a global assets indicator: re-assessing the assets indicator in the global multidimensional poverty index - Vollmer, F; Alkire, S (Oxford Poverty and Human Development Initiative, 2018)
This paper explains the revision of the assets indicator of the updated global Multidimensional Poverty Index (global MPI), which was launched just before the 73rd Session of the United Nations General Assembly in September 2018. The joint decision of the United Nations Development Programme (UNDP) and the Oxford Poverty and Human Development Initiative (OPHI) to revise the global MPI in 2018 to align it with the Sustainable Development Goals and to best monitor progress towards “leaving no one behind” provided the opportunity to assess the statistical validities of the assets indicator contained in the Original MPI, jointly designed by OPHI and UNDP Human Development Report Office (HDRO) in 2010, and an assets indicator included in an Innovative MPI, which was developed by UNDP HDRO in 2014. Further, considering the improvements in many Demographic and Health Surveys, Multiple Indicators Cluster Surveys and selected national surveys in recent years, from which the global MPI is constructed, the revision also offered an occasion to assess whether the inclusion of additional assets would add value to a revised asset index for the updated global MPI 2018. Taking into account a blend of inputs, including statistical test results, public consultations, normative reasoning and substantive trial measures of possible asset indices as outlined in detail in this paper, the revised assets indicator maintained the structure of the Original MPI, but added computer and animal cart as additional items. Here we explain the reasons and delineate the many decisions that were taken along the way.